High vacuum PVD technique for enhancing ZnO thin films: optical and electrical characterization / Wan Amir Syauqi Wan Razali ... [et al.] - Wan Razali, Wan Amir Syauqi; Nadzri, Allina; Md Sani, Junaidah; Harif, Muhammad Najib (Penerbit UiTM (UiTM Press), 2024)
This study explores the fabrication of high-quality zinc oxide (ZnO) thin films using a high-vacuum deposition process. ZnO, a material of significant interest due to its extensive applications, necessitates reliable deposition techniques. The research is segmented into three stages: sample preparation and cleaning, fabrication, and characterization. Soda lime glass (SLG) substrates were utilized, with metallic Zn deposited via physical vapor deposition (PVD) using electron beam deposition (e-Beam). Post-deposition, the Zn films were annealed at various temperatures to induce oxidation into ZnO. The resultant films were analyzed through UV-VIS spectrophotometry and Hall Effect measurements to assess their optical and electrical properties. The primary aim was to develop ZnO thin films using e-Beam technology in a high vacuum environment (1 x 10-5 Torr), with a novel focus on reducing annealing time for ZnO thin films at elevated temperatures under atmospheric pressure. Additionally, the study provides an in-depth understanding of the relationship between deposition parameters and film qualities, enabling precise tuning of ZnO thin film characteristics. This research holds significant potential for enhancing the performance of optoelectronic devices, such as solar cells and LEDs. The controlled deposition method established here can be commercialized, facilitating the mass production of high-quality ZnO thin films with tailored properties to meet the growing industrial demand.